Investigating the Impact of Spatial Habitat and Environmental Quality on Improving Satisfaction of Citizens from Localities (Case study: Keshavarz District 6th District of Tehran) - Elmira Azimi; hosin Mobara; maryam farzadmanesh (تحقیقات کاربردی علوم جغرافیایی)
The emergence of a variety of inequalities, widespread poverty, malnutrition and ... were examples of the effects of urbanization. For this reason, many scholars and experts have focused on the quality of life, in order to improve living conditions and improve the quality of life of human beings. Many studies show that satisfaction with different dimensions and characteristics of the neighborhood affects residents' quality of life. Considering that satisfaction with life, i.e., the full satisfaction of all parts of life, if this kind of satisfaction does not develop among residents, more serious problems such as intra-urban migration, severe class contradictions and the problem of uplifting and down-town faces Accepts. Therefore, identifying the effective factors on residential satisfaction in each neighborhood, which is in accordance with the needs of the residents of that neighborhood, is one of the main goals of urban planners in order to increase residential satisfaction. The purpose of this study was to investigate the effect of location and quality of environment on improving citizens' satisfaction from neighborhoods. The research method was descriptive-analytic, data collection method, library and survey, sample size was estimated 315 by Cochran formula. In order to test the hypotheses presented in this study, structural equation modeling was used in Lisrel software environment. The results of this study indicate that spatial sense of belonging and quality of environment have a significant effect on residents' satisfaction with the neighborhood.